Health Sciences Research in Medical Education - Maskey, MK (Journal of Nepal Health Research Council, 2009)
DOI: 10.3126/jnhrc.v7i1.2296 Journal of Nepal Health Research Council Vol. 7, No. 1, 2009 April 54-57